Pelatihan Web Programming di SMK Dr Cipto Mangunkusumo Perdagangan - Poningsih Poningsih; Sundari Retno Andani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The development of information and technology is currently so fast. Along with these developments, users must be up to date in accordance with the times. Currently there are many web applications that can be used as needed. To balance the development of information technology with the needs of users, it is very necessary for human resources who are able to provide creative ideas and high innovation. SMK Dr. Cipto Trade has national talents who are competent in the field of information technology. Student / I SMK Dr. Cipto Trade, especially the RPL Department, has sufficient capabilities in the field of information technology, including the web. However, the students' abilities still need to be added and sharpened. One way is to provide them with web programming training using HTML and the PHP programming language. The results of this training show a significant increase in ability.